Organic Amendments promote saline-alkali soil desalinization and enhance maize growth - Wang, Yaqi; Gao, Ming; Chen, Heting; Chen, Yiwen; Wang, Lei; Wang, Rui (Frontiers in Plant Science, 2023)
Secondary soil salinization in arid and semi-arid regions is a serious problem that severely hampers local agricultural productivity and poses a threat to the long-term sustainability of food production. the utilization of organic soil amendments presents a promising approach to mitigate yield losses and promote sustainable agricultural production in saline-alkali soil. In this study, we established four distinct treatments, chemical fertilizer (CK), humic acid with chemical fertilizer (HA), carboxymethyl cellulose with chemical fertilizer (CMC), and amino acid with chemical fertilizer (AA), to elucidate their respective impacts on the reclamation of saline soil and the growth of maize. The findings of our study reveal notable variations in desalination rates within the 0-40 cm soil layer due to the application of distinct soil amendments, ranging from 11.66% to 37.17%. Moreover, application of amendments significantly increased the percentage of soil macro-aggregates as compared to the CK treatment. Furthermore, HA and AA treatments significantly augmented soil nutrient content (HA: 48.07%; AA: 39.50%), net photosynthetic rate (HA: 12.68%; AA: 13.94%), intercellular CO2 concentration (HA: 57.20%; AA: 35.93%) and maize yield (HA:18.32%; AA:16.81%). Correlation analysis and structural equation modeling unveiled diverse mechanisms of yield enhancement for HA, CMC, and AA treatments. HA enhanced yield by increasing organic matter and promoting soil aggregate formation, CMC improved soil water content and facilitated salt leaching due to its excellent water-holding properties, while AA increased yield by elevating soil organic matter and effective nitrogen content. Among the array of soil amendment materials scrutinized, HA treatment emerged as the most promising agent for enhancing soil conditions and is thus recommended as the preferred choice for treating local saline soils.